Pengaruh Current Ratio, Debt To Asset Ratio, Dan Operating Capacity Terhadap Financial Distress Dengan Return On Asset Sebagai Variabel Moderasi Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Tahun 2019-2023 - Tasya Amanda; Azwansyah Habibie; Yani Suryani (Journal of Innovative and Creativity, 2025)
This study examines and analyses the effect of three independent variables: Current Ratio, Debt-to-Asset Ratio, and Operating Capacity on Financial Distress, with Return on Assets as a moderating variable. The population used in this study were property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Purposive sampling was used to select 41 companies. The analytical techniques used were descriptive analysis and multiple linear regression analysis. The data were sourced from the companies' financial statements and processed using SPSS version 26. The results show that the Current Ratio, Debt-to-Asset Ratio, and Operating Capacity significantly influence Financial Distress. Return on Assets moderated the influence of the Current Ratio and Debt-to-Asset Ratio on Financial Distress. However, Return on Assets did not moderate the impact of Operating Capacity on Financial Distress.